Is Speech-Language Pathology’s Clinical Training Responsive to the South African Context? (Journal of Decolonising Disciplines, 2021)
The absence of equitable speech- language pathology services for South Africa’s black majority has triggered a need to decolonise the clinical curriculum. The purpose of this study was to describe the experiences of clinical educators when supervising diverse students in various community settings. A qualitative approach was employed, including interviewing seven clinical educators in speech-language pathology, in a focus group. The responses from the discussions were analysed using thematic content analysis. The participants highlighted themes and certain challenges (i) Differences (ii) discomfort (iii) clinical preparation and (iv) critical engagement. These results highlight a mismatch between the efforts of the department to transform and the experiences of the clinical educators. The results further highlight the need for the department to support clinical educators in developing a mind-set of change, of shifting the power dynamics and valuing intercultural communication.
Keywords: Clinical Education; Decolonisation; Speech-language Pathology